Development of regenerative piezoelectric linear generator for alternative power generation - Siti Nur Sakinah, Jamaludin (2011)
The unique ability of piezoelectric materials shows their potential in harvesting power for the application of micro to miniature power source range of devices in the industry. Focus on the suspension operating system which produces waste vibrating energy as a source of power, a conceptual design of a regenerative piezoelectric linear generator was developed by considering some factors including the dimensions, shapes, maintenance convenience and material behaviour. In this project, piezoelectric plate used in a buzzer was modified to be a multilayer stack as an actuation element for the regenerative piezoelectric linear generator which able to supply power for certain applications. The performance of the fabricated prototype had been tested on a specific testing rig within some inputs variables in terms of different force magnitude, speed and load duration. The preliminary testing on the real system of the generator also performed where two loadings from 50kg’s and 80kg’s person bouncing had been considered. The experimental testing had agreed the hypothesis made where the model configurations and the mechanism of power harvesting implemented could influence the power output achieved by the system. The proposed design is proved able to achieve more power within more smart material thickness and layers. It also able to works within different frequencies and load duration that refer to variety of road conditions we have in our country. The average output power achieved was reached until 1.33mW and the value could be enhanced within the addition of piezoelectric plate thickness and layers. This thesis elaborated the whole process of designing the generator from the first brainstorming of conceptual design until the recommendation of the designed model.